AI-enabled programming, networking, and cybersecurity - Santos, Omar (Pearson, 2024)
AI-Enabled Programming, Networking, and Cybersecurity is for programmers, developers, networking, or security professionals looking to use AI tools. AI-powered tools like ChatGPT, GitHub Copilot, Cursor, LangChain, and other AI models are changing the landscape of cybersecurity, programming, networking, and beyond. This course covers the introduction to the AI models, focusing on ChatGPT for cybersecurity education, GitHub Copilot and Cursor for programming support, and other AI models that have proven useful for learning and work enhancements, and explores the practical applications of these tools, emphasizing how to ask effective questions, interpret answers, and engage in deeper learning.
Online resource; title from title details screen (O'Reilly, viewed October 10, 2024)
Keywords: Artificial intelligence; Computer programming; Computer networks; Computer security; Computer networks -- Security measures; Intelligence artificielle; Programmation (Informatique); Sécurité informatique; Réseaux d'ordinateurs; Sécurité; Mesures; artificial intelligence; computer programming; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet